A20 of nucleus pulposus cells plays a self-protection role via the nuclear factor-kappa B pathway in the inflammatory microenvironment. Issue 5 (May 2020) - Peng, Xin; Zhang, Cong; Bao, Jun-Ping; Zhu, Lei; Shi, Rui; Xie, Zhi-Yang; Wang, Feng; Wang, Kun; Wu, Xiao-tao
Abstract : Aims: Inflammatory response plays a pivotal role in the pathophysiological process of intervertebral disc degeneration (IDD). A20 (also known as tumour necrosis factor alpha-induced protein 3 (TNFAIP3)) is a ubiquitin-editing enzyme that restricts nuclear factor-kappa B (NF-κB) signalling. A20 prevents the occurrence of multiple inflammatory diseases. However, the role of A20 in the initiation of IDD has not been elucidated. The aim of the study was to investigate the effect of A20 in senescence of TNF alpha (TNF-α)-induced nucleus pulposus cells (NPCs). Methods: Immunohistochemical staining was performed to observe the expression of A20 in normal and degenerated human intervertebral discs. The NPCs were dissected from the tail vertebrae of healthy male Sprague-Dawley rats and were cultured in the incubator. In the experiment, TNF-α was used to mimic the inflammatory environment of IDD. The cell viability and senescence were examined to investigate the effect of A20 on TNF-α-treated NPCs. The expression of messenger RNA (mRNA)-encoding proteins related to matrix macromolecules (collagen II, aggrecan) and senescence markers (p53, p16). Additionally, NF-κB/p65 activity of NPCs was detected within different test compounds. Results: The expression of A20 was upregulated in degenerate human intervertebral discs. The A20 levels of NPCs in TNF-α inflammatory microenvironments were dramatically higher than those of the control group. TNF-α significantly decreased cell proliferation potency but increased senescence-associated beta-galactosidase (SA-β-Gal) activity, the expression of senescence-associated proteins, the synthesis of extracellular matrix, and G1 cycle arrest. The senescence indicators and NF-κB/p65 expression of A20 downregulated group treated with TNF-α were significantly upregulated compared to TNF-α-treated normal NPCs. Conclusion: A20 has a self-protective effect on the senescence of NPCs induced by TNF-α. The downregulation of A20 in NPCs exacerbated the senescence of NPCs induced by TNF-α. Cite this article: Bone Joint Res. 2020;9(5):225–235.